Circulating tumor cells in metastatic breast cancer: clinical relevance and biological potential - Polasik, Arkadius Andreas; Schneeweiss, Andreas (Current opinion in obstetrics and gynecology, 2019)
Purpose of reviewThe possibility of tumor dissemination through the blood system has been known for years. Circulating tumor cells (CTCs) are detectable in the peripheral blood of patients with early as well as metastatic breast cancer. The prognostic relevance of this biomarker has already been des